Optimización del sistema de explotación para la extracción de materiales árido y pétreos del área minera “DYNA código 30000457”, ubicada en la parroquia Arenillas, cantón Arenillas, provincia de El Oro. - Rojas Troya, Jordy Joao (2021)
This work was carried out in the Dyna quarry, code 30000457, located in Arenillas parish, Arenillas canton, province of El Oro, and its purpose is to optimize the exploitation system for the extraction of aggregate and stone materials. To carry out this purpose, we started with a diagnosis of the works that are developed with the current exploitation system, as well as a survey of geological and topographic information, so that from this evaluation we can determine which are the factors to be optimized. The description of the processes and activities corresponding to the current exploitation system was carried out through direct observation and field records, technically detailing its operation and machinery used. In addition, the yield and production were determined, as well as the monetary value of this production, establishing the cost per cubic meter of extracted material. Once the optimized exploitation system was defined, the processes and activities were described, taking into account technical parameters to improve its operation. The calculation of the yield, production of the machinery under these conditions and its monetary value, allowed determining the cost per cubic meter of material extracted in this system. Finally, an economic estimation of the implementation or adjustments made in the different processes and activities for the two study fronts was made. Consequently, the proposed exploitation design will allow a better control of the mining operations, with better working conditions, safeguarding the integrity of the personnel and the machinery used, guaranteeing an adequate technical and economic operation. Key words: Optimization, aggregates, stone, processes, yield, production, monetary, technical and economic operation.